Study of structure and properties of platinum(II) chloride complexes with (2-alkyltetrazol-5-yl)acetic acid by quantum chemistry and NMR-spectroscopy methods - Matulis, Vitaly E.; Ragoyja, Ekaterina G.; Serebryanskaya, Tatiyana V.; Grigoriev, Yuri V.; Ivashkevich, Oleg A. (Journal of the Belarusian State University. Chemistry, 2019)
It has been shown that the WP04 functional in combination with moderate basic sets 6-31G(d) and SDD allows to calculate characteristics of 1H NMR-spectrum of metal complexes with ligands based on tetrazole derivatives with high accuracy, which can be used to assign signals in the NMR-spectra. The process of hydrolysis of the isomeric platinum(II) chloride complexes with (2-isopropyltetrazol-5-yl)acetic acid has been investigated using the methods of quantum chemistry and NMR-spectroscopy. An explanation of the changes of signals in the 1H NMR-spectra of the considered complexes during their hydrolysis is given.
Keywords: tetrazole; complexes; DFT; NMR-spectra; geometrical structure